Temperature and Precipitation More Than Tree Cover Affect the Distribution Patterns of Epiphytic Mosses within the Orthotrichaceae Family in China and Adjacent Areas - Fialová, Lucie; Plášek, Vítězslav; Klichowska, Ewelina; Guo, Shuiliang; Nobis, Marcin (Plants (Basel, Switzerland), 2023)
Epiphytes, including vascular and non-vascular, constitute a large part of global plant biodiversity. Distribution of obligatory epiphytic bryophytes results from climate and local habitat conditions. The most important epiphytic bryophytes and at the same time poorly investigated and taxonomically problematic ones belong to the family Orthotrichaceae. Epiphytic mosses are also ideal organisms for species modelling, because of having no roots, they are highly dependent on external environmental conditions. For this purpose, we used the ecological niche modelling approach to define their potential distribution in China and adjacent areas and explore factors that shape this distribution. We used 617 occurrence records of 23 species from six genera within the Orthotrichaceae family. Our results suggest that the distribution of members of the Orthotrichaceae family is predominantly affected by bioclimatic variables, especially bio10 (mean temperature of the warmest quarter), bio15 (precipitation seasonality), bio18 (precipitation of the warmest quarter), bio19 (precipitation of the coldest quarter), bio9 (mean temperature of the driest quarter), and bio2 (mean diurnal range). However, the distribution of particular genera is ruled by a different set of those variables. The distribution of two genera (Leratia and Ulota) is also highly influenced by land cover (especially mixed/other trees), whereas human footprint shows a moderate contribution to models of three genera (Lewinskya, Orthotrichum, Nyholmiella). Based on the occupied climatic niche and distribution patterns, representatives of the studied family are divided into two groups. The 'western-montane group' is characterised by lower temperatures and lower precipitation whereas the 'eastern-lowland' group' by more humid and warmer conditions.
Keywords: distribution maps; ecological niche modelling; Asia; Macromitrium; bryophytes; Leratia; Ulota; Nyholmiella; Lewinskya; Orthotrichum